Do no harm in due process – a historical analysis of social determinates of institutionalization in the USA. Issue 4 (December 2021) - Durns, Tyler
Involuntary hospitalization has been a fundamental function of psychiatric care for mentally ill persons in the USA for centuries. Procedural and judicial practices of inpatient psychiatric treatment and civil commitment in the USA have served as a by-product of socio-political pressures that demanded constant reform throughout history. The origin of modern commitment laws can best be understood through the lens of cultural paradigms that led to their creation and these suggest caution for future legislative amendments.